Fondements des analyses de flux de matières et d’énergie et typologies d’applications pour la gouvernance des territoires et des organisations - Benoit Ribon; Dominique Badariotti; René Kahn (VertigO)
Material and energy flow analysis (MEFA) is a helpful tool for understanding systems and is essential in several applications. It is based on accounting approach of flows and on mass and energy conservation principles. MEFA was particularly important for industrial development, but it is now also very useful to tackle ecological issues. Indeed, it allows for describing material dynamics and interactions with the environment at different scales : from micro level for an industrial process or an organisation (company, administration ...) to macro level for a territory (city, region, country ...). MEFA can also be performed at a transversal scale when realising a life-cycle inventory for a given product. Even with specific methods for each of those scales, the analysis have common basis and can have similar uses. We identified in literature different typologies of applications : environmental impacts assessment, process optimization, study of material dispersion and deposit, identification of local resources, legislative contribution, communication on environmental impacts and progresses, urbanism consideration, building of a territory shared vision including circular economy and resiliency consideration. MEFA have thus a large panel of applications to tackle sustainable development according different societal and technical perspectives. Hence, it should be included among the governance tools of organisations and territories. However this will be possible only if we success to overcome several difficulties : managing a big amount of data ; making feedbacks accessible to uninitiated people through different understanding frameworks ; developing legislation in favour of material accounting ; and gathering various competences in order to correctly perform and interpret MEFA.